Pendampingan dan Peran TPQ untuk Meningkatkan Baca Al-Qur’an di Dusun Pengkol Desa Ngrami - Muhammad; Zakiya Nur Fadhila Asshafy; Qurratul ‘Ain; Kholel Imammudin; Muhammad Syafiqul Fikri; Moh Rois Utomu Maulidi; Ainir Rohmah (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2025)
This community service activity aims to improve the ability to read the Qur'an among children in Pengkol Hamlet, Ngrami Village, through guidance and the role of the Qur'an Education Park (TPQ). The background of this research is the low ability to read the Qur'an due to limited teaching methods, lack of intensive guidance, low motivation to learn, and inadequate TPQ facilities. This research uses a qualitative approach with descriptive methods and Participatory Action Research (PAR) involving TPQ managers, teachers, and students. The results showed that children in Pengkol Hamlet generally have low Al-Qur'an reading skills, with many errors in the pronunciation of makharijul letters and incorrect application of reading laws. The presence of KDLK students in assisting teaching has made the learning process more conducive and allowed for creative activities such as competitions. Factors influencing the effectiveness of TPQ include teacher quality and competence, curriculum and learning methods, and family and community support. The main obstacle found is the large number of children (40 children) which is not proportional to the number of teachers. This community service is expected to create significant social change in improving sustainable Qur'an reading skills and strengthening religious values in the community.